KONDISI TERUMBU KARANG DI PULAU MATAS TAMAN NASIONAL TELUK CENDERAWASIH - Edward Sembiring; Astriet Y Manangkoda; Agus Susanto (LPPM Universitas Terbuka, 2010)
Corals is the one of typical ecosystem that is at tropic waters that tremendously necessary for directness biodiversity at coast and ocean area. Teluk Cenderawasih National Park having corals more or less 80.000 hectares. But such data and information about corals condition stills less in particularly at Core Zone. One of Core Zone that needs to be done to inventory and identification activity is Matas Island and its vicinity. Executed research with Manta Tow and Line Intercept Transect (LIT) Methods. Result of the observation by use of Manta Tow method can be categorized that medium corals category, with life corals cover as big as 46.25 % of 24 observing trajectories. Observation in LIT Method on depth 3 meters, it has been very good corals cover area (91.02 %), and on depth 10 meters, it has been medium category (39. 48 %). Corals Mortality Index is little relative ranging from 0.03-0.06, thats the mean condition of ecosystem in Matas Island is healthy.